Penggunaan Media Pembelajaran Powerpoint Interaktif Untuk Peningkatan Prestasi Belajar Bahasa Inggris: Materi Narrative Text Reading Siswa MPLB SMK Negeri 3 Linggabuana - Anggorowati, Yuratin Dewi (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2022)
The results of the study using interactive powerpoint learning media can improve English learning achievement in reading narrative text material in the field of office management and business services expertise for class X students of SMK Negeri 3 Linggabuana Purwakarta in the 2022/2023 academic year. It can be proven that in cycle I there were only 15 students who were able to achieve KKM or 39%. In the second cycle of learning activities, 65% or 25 students reached the KKM with an average score of 67.23. Furthermore, in cycle III learning activities it can be proven that the use of interactive Powerpoint learning media can increase student learning activity and learning achievement which is very significant. This can be seen based on statistical analysis of all students achieving KKM = 65 or 100% have achieved KKM = 65 with an average grade of 78.28